Human mesenchymal stem cells labelled with dye-loaded amorphous silica nanoparticles: long-term biosafety, stemness preservation and traceability in the beating heart. Issue 1 (December 2015) - Gallina, Clara; Capelôa, Tânia; Saviozzi, Silvia; Accomasso, Lisa; Catalano, Federico; Tullio, Francesca; Martra, Gianmario; Penna, Claudia; Pagliaro, Pasquale; Turinetto, Valentina; Giachino, Claudia
Abstract Background Treatment of myocardial infarction with mesenchymal stem cells (MSCs) has proven beneficial effects in both animal and clinical studies. Engineered silica nanoparticles (SiO2 -NPs) have been extensively used as contrast agents in regenerative medicine, due to their resistance to degradation and ease of functionalization. However, there are still controversies on their effective biosafety on cellular systems. In this perspective, the aims of the present study are: 1) to deeply investigate the impact of amorphous 50 nm SiO2 -NPs on viability and function of human bone marrow-derived MSCs (hMSCs); 2) to optimize a protocol of harmless hMSCs labelling and test its feasibility in a beating heart model. Results Optimal cell labelling is obtained after 16 h exposure of hMSCs to fluorescent 50 nm SiO2 -NPs (50 µg mL−1 ); interestingly, lysosomal activation consequent to NPs storage is not associated to oxidative stress. During prolonged culture hMSCs do not undergo cyto- or genotoxicity, preserve their proliferative potential and their stemness/differentiation properties. Finally, the bright fluorescence emitted by internalized SiO2 -NPs allows both clear visualization of hMSCs in normal and infarcted rat hearts and ultrastructural analysis of cell engraftment inside myocardial tissue. Conclusions Overall, 50 nm SiO2 -NPs display elevated compatibility with hMSCs in terms of lack of cyto- and genotoxicity and maintenance of important features of these cells. The demonstrated biosafety, combined with proper cell labelling and visualization in histological sections, make these SiO2 -NPs optimal candidates for the purpose of stem cell tracking inside heart tissue.